KOLONISASI FUNGI PADA SERASAH DAUN Avicennia marina DI DESA NELAYAN SEBERANG KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG SUMATERA UTARA - Risda Farida Lubis; Yunasfi Djayus; Amanatul Fadhilah (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The village of Paluh Kurau is a village located in Hamparan Perak District in Belawan, North Sumatera. The village is located opposite the harbor, the amount of benefits found in the mangrove forest ecosystem makes it highly vulnerable to environmental degradation and community activities and port activities near the village of Paluh Kurau. This study aims to determine the type of fungi contained in leaf litter Avicennia marina in Nelayan Seberang Village Hamparan Perak District Deli Serdang District of North Sumatera. This study was conducted in January-March 2017. The results showed that the type of fungi found in Avicennia marina leaf litter in Nelayan Seberang Village Hamparan Perak Subdistrict Deli Serdang District of North Sumatera there are 12 types of fungi namely Culvularia lunata, Fusarium sp., Fusarium verticilliodes, Aspergillus sp. 1, Aspergillus sp. 2, Aspergillus niger, Trichoderma harzianum, Pestalotia sp., Penicilium sp., Scytalidium lignicola, unidentified fungi 1, and unidentified fungi 2.Keywords: Mangrove, Leaf Litter, Avicennia marina, Village of Nelayan Seberang, Hamparan Perak